The Predictive Effect of Health Examination in the Incidence of Diabetes Mellitus in Chinese Adults: A Population-Based Cohort Study - Xiaomin Fu; Yingmin Jia; Jing Liu; Qinghua Lei; Lele Li; Nan Li; Yanyan Hu; Shanshan Wang; Hongzhou Liu; Shuangtong Yan (Journal of Diabetes Research)
Background. The incidence of diabetes mellitus (DM) was increasing in recent years, and it is important to screen those nondiabetic populations through health examination to detect the potential risk factors for DM. We aimed to find the predictive effect of health examination on DM. Methods. We used the public database from Rich Healthcare Group of China to evaluate the potential predictive effect of health examination in the onset of DM. The colinear regression was used for estimating the relationship between the dynamics of the health examination index and the incident year of DM. The time-dependent ROC was used to calculate the best cutoff in predicting DM in the follow-up year. The Kaplan-Meier method and Cox regression were used to evaluate the HR of related health examination. Results. A total of 211,833 participant medical records were included in our study, with 4,172 participants diagnosing as DM in the following years (among 2-7 years). All the initial health examination was significantly different in participants’ final diagnosing as DM to those without DM. We found a negative correlation between the incidence of years of DM and the average initial FPG (r=−0.1862, P<0.001). Moreover, the initial FPG had a strong predictive effect in predicting the future incidence of DM (AUC=0.961), and the cutoff was 5.21 mmol/L. Participants with a higher initial FPG (>5.21 mmol/L) had a 2.73-fold chance to develop as DM in follow-up (95%CI=2.65–2.81, P<0.001). Conclusion. Initial FPG had a good predictive effect for detecting DM. The FPG should be controlled less than 5.21 mmol/L.